A typology of company behaviour in the internationalisation process (a network approach) - Fonfara, Krzysztof (Economics and Business Review, 2011)
The aim of the paper is to propose a typology of company behaviour in the internationalisation process and to verify it empirically in the context of the company's success. On the basis of the established characteristics, a number of options of company model behaviour were distinguished. These were subsequently subjected to an initial evaluation on the basis of experts' opinions. This resulted in the identification and selection of four possible types of company behaviour in the internationalisation process. A mail survey was conducted in which a sample of 2,000 firms engaged in international operations and based in Poland was randomly selected on the basis of a database from Kompass Poland. The response rate was 14%. The paper, which contains a number of observations made on the basis of empirical results, aims at explaining the nature of relations between a specific type of company behaviour in the internationalisation process and the company's performance. (original abstract)